2017
DOI: 10.21037/acs.2017.09.15
|View full text |Cite
|
Sign up to set email alerts
|

Pros and cons of transcatheter aortic valve implantation (TAVI)

Abstract: Transcatheter aortic valve implantation (TAVI) or replacement (TAVR) was recently approved by the FDA for intermediate risk patients with severe aortic stenosis (AS). This technique was already worldwide adopted for inoperable and high-risk patients. Improved device technology, imaging analysis and operator expertise has reduced the initial worrisome higher complications rate associated with TAVR, making it comparable to surgical aortic valve replacement (SAVR). However, many answers need to be addressed befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 54 publications
2
26
0
1
Order By: Relevance
“…SAVR remains the golden standard for low-risk and intermediate-risk patients. However, recently TAVR has been expanded to intermediate [40] and low-risk patients [29]. For example, the SAPIEN 3 and CoreValve Evolut R TM received CE-mark approval in 2016 to treat intermediate-risk patients with TAVR.…”
Section: Expert Opinionmentioning
confidence: 99%
“…SAVR remains the golden standard for low-risk and intermediate-risk patients. However, recently TAVR has been expanded to intermediate [40] and low-risk patients [29]. For example, the SAPIEN 3 and CoreValve Evolut R TM received CE-mark approval in 2016 to treat intermediate-risk patients with TAVR.…”
Section: Expert Opinionmentioning
confidence: 99%
“…The stroke rates may be further impacted with the recent FDA approval of the embolic protection devices in TAVR . Another possible explanation is the lower incidence of AF in the TAVR group of our study, which was found to be a predictor of stroke . Furthermore, a recent study by Reinohl et al observed higher stroke rate after SAVR in CABG patients compared to those without history of CABG…”
Section: Discussionmentioning
confidence: 46%
“…The susceptibility to AV block depends on the surgical technique in SAVR, but it is device specific for TAVR, while others include aortic root characteristics and implantation depth . PPI has not been found to increase the risk of mortality, at least out to 2 years, although it can affect quality of life by increasing the duration of hospitalization and readmissions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were hardly any substantive differences between the inoperable and high-risk operable groups (Table 1). [6] Secondly, occurrence of comorbidities and frailty were not uniform in the TAVI and non-TAVI groups [7] in Cohort B. Incidence of comorbidities was noticeably higher in the surgical AVR group (Table 2) [6].…”
mentioning
confidence: 96%